OP0042 LONG-TERM EFFECTS OF SYNERGETIC B CELL IMMUNOMODULATION WITH RITUXIMAB AND BELIMUMAB COMBINATION TREATMENT IN SEVERE, REFRACTORY SLE: TWO YEAR RESULTS. (June 2019) - Kraaij, Tineke; Arends, E.J.; Dam, Laura van; Kamerling, Sylvia; Daele, Paul L.A. van; Bredewold, Obbo Winne; Ray, Argho; Bakker, Jaap; Bajema, Ingeborg; Scherer, Hans Ulrich; Huizinga, Thomas; Rabelink, Ton; et al.
Abstract : Background: We conducted a phase 2, proof-of-concept study (SynBioSe study) in which we combined rituximab and belimumab (RTX+BLM) for treatment of SLE patients with severe, refractory disease. We have previously reported that RTX+BLM effectively reduced relevant anti-nuclear autoantibodies (ANAs) and showed a clinical response at 24 weeks 1 . Objectives: The aim of the present study is to investigate the long-term immunological and clinical effects of RTX+BLM in severe, refractory SLE patients. Methods: Fifteen severe, refractory SLE patients were included and followed for 2 years. Patients received RTX at week 0 and 2 and BLM at week 4, 6, 8 and then 4-weekly until week 104. Clinical response was assessed by achievement of low level of disease activity (LLDAS). By using specific antibody assays and high sensitivity flowcytometry (HS-FACS), we longitudinally followed, respectively, levels of SLE-specific ANAs and B-cell subsets. Results: Ten patients (67%) showed a good clinical response after 24 weeks, referred to as 'responders'. Two of these patients (13%) switched treatment after 24 weeks due to a pregnancy wish and 8 patients (53%) continued study treatment throughout the complete 2 years of follow-up. Five patients (33%) discontinued treatment due to persistent LN (n=2), major flare (n=2) or relapsing minor flare (n=1), together referred to as 'non-responders'. Responders achieved LLDAS at a median of 24 weeks [range 12-36] and remained in LLDAS for 76 weeks [56-92] out of 104 weeks of follow-up. In 7 patients with active LN, 6 attained a complete renal response. In responders, ANAs showed significant and specific reduction throughout 2 years with achievement of seronegative anti-dsDNA immunofluorescence in 6 out of 6 anti-dsDNA positive patients at baseline while total IgG, anti-tetanus and anti-rubella antibodies remained stable. By using HS-FACS, a median decrease of 97% [-99;+35] CD19+ B-cell depletion was achieved at 24 weeks. Long-term follow-up showed that B-cell repopulation was inhibited throughout 2 years with a persistent median decrease of 84% [-92;+22] compared to baseline. Further analysis of B-cell subsets revealed that in the responders, double negative (DN) B cells (CD27-IgD-) reached maximum depletion at 4 weeks (median 1.09*10 6 cells/liter [range 0.23*10 6 -4.31*10 6 ]), which lasted up to week 72 with a median of 1.26*10 6 cells/liter [0.79*10 6 -4.11*10 6 ] at week 72, similar to values at nadir. This was in contrast to non-responders, where maximum depletion of DN B-cells was reached at 12 weeks (0.48*10 6 [0.17*10 6 -5.86*10 6 ], after which these cells increased to 2.29*10 6 [0.49*10 6 -4.39*10 6 ] at 24 weeks. Conclusion: Over 2 years follow-up, RTX+BLM for severe, refractory SLE patients prevented complete B-cell repopulation with persistent and specific reduction of ANAs. Clinical response was observed in 67% of patients and treatment discontinuation due to high disease activity was associated with early repopulation of DN B-cells. These data warrant further studies on clinical and immunological benefits of combination treatment RTX+BLM. Reference: [1] Kraaij T, Kamerling SWA, de Rooij ENM, et al. The NET-effect of combining rituximab with belimumab in severe systemic lupus erythematosus. J Autoimmun2018;91:45-54.doi: 10.1016/j.jaut.2018.03.003. Trial registration: ClinicalTrials.gov NCT02284984 Disclosure of Interests: Tineke Kraaij: None declared, E.J. Arends: None declared, Laura van Dam: None declared, Sylvia Kamerling: None declared, Paul LA van Daele: None declared, Obbo Winne Bredewold: None declared, Argho Ray: None declared, Jaap Bakker: None declared, Ingeborg Bajema Consultant for: GSK, Hans Ulrich Scherer Grant/research support from: Sanofi, BMS, Thomas Huizinga Consultant for: Merck, UCB, Bristol Myers Squibb, Biotest AG, Pfizer, GSK, Novartis, Roche, Sanofi-Aventis, Abbott, Crescendo Bioscience Inc., Nycomed, Boeringher, Takeda, Zydus, Epirus, Eli Lilly, Ton Rabelink: None declared, Cees van Kooten: None declared, Y.K. Onno Teng Grant/research support from: Received lecture fees/consultancy fees from GSK and from Aurinia Pharmaceuticals.